Optimization of Educational Da’wah on Social Media as a Communication Strategy for Islamic Religious Education for Gen Z in High Schools in Blitar City - Muhammad Fikri 'Ainun Najib; Miftakhul Rohman (Journal of Communication Studies, 2025)
The digital revolution has influenced the pattern of Islamic da’wah communication, especially among Generation Z, who grew up in a social media ecosystem. Platforms such as TikTok, Instagram, and YouTube have now become the main sources of religious information for high school students. This study aims to analyze effective educational da’wah communication strategies on social media to support Islamic Religious Education (PAI) learning. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation at three high schools in Blitar City: SMA 1, SMA 2, and SMA 3. The data analysis technique in this research follows the stages of data reduction, data presentation, and drawing conclusions. Data reduction was carried out by sorting and simplifying the results of observations, interviews, and documentation deemed relevant to the research focus. Next, data presentation was arranged systematically in a narrative form to make it easier for researchers to fully understand the problem’s context. The final stage involved inductive conclusion-drawing based on findings in the field to answer the research problem statements.   The study’s results show that social media can enhance students’ understanding, participation, and interest in PAI material when conveyed through visual, communicative, and contextual content. PAI teachers play a crucial role as facilitators in designing digital da’wah that is not only aesthetically appealing but also strengthens students’ Islamic character. This study recommends an integration of the PAI curriculum that is adaptive to digital technology as well as digital competency training for teachers as efforts to develop relevant and impactful da’wah strategies.